The Importance of Induced Pluripotent Stem Cell Research in Medical Science - Agustina Kadaristiana (Cermin Dunia Kedokteran, 2015)
The degenerative diseases that are currently incurable, such as heart disease, stroke, and diabetes, became the global leading causes of death in 2010 and 2011. This fact urges scientists to find alternative treatment for those conditions. In 2006, Takahashi and Yamanaka succeeded in generating an alternative source of stem cells called induced pluripotent stem cell (iPSC). This groundbreaking work holds the promise of new ways to repair cell damage and improve treatment of currently untreatable conditions without raising ethical debates. Many scientists still question whether iPSC is completely interchangeable with ESC in terms of pluripotency and cell mortality. Indeed, iPSC clones and ESC clones have overlapping degrees of variation. It can be concluded that different cell lines will be best suited for different applications. This essay will describe the development stem cell research, comparison between IPSC and ESC, the promise of IPSC technology and current challenges in the applications of iPSCs.Penyakit degeneratif yang saat ini belum dapat disembuhkan, seperti penyakit jantung, stroke, dan diabetes, menjadi penyebab kematian utama di dunia pada tahun 2010 dan 2011. Fakta ini mendorong peneliti untuk mencari terapi yang bersifat kuratif. Tahun 2006, Takahashi dan Yamanaka berhasil menemukan sumber alternatif sel punca bernama sel punca pluripoten yang diinduksi/Induced Pluripotent Stem Cell (iPSC). Penemuan besar ini memberi harapan dalam memperbaiki sel rusak dan meningkatkan kualitas terapi penyakit yang belum bisa disembuhkan tanpa menimbulkan perdebatan etika. Masih dipertanyakan apakah pluripoten dan kematian sel klon sel iPS sama dengan sel punca embrionik (Embrionic Stem Cells/ ESC). Ternyata, terdapat variasi tumpang tindih antara klon iPSC dan ESC. Dapat disimpulkan bahwa sel yang berasal dari alur berbeda, cocok untuk penggunaan yang berbeda. Makalah ini bertujuan untuk memaparkan perkembangan penelitian sel punca, perbandingan antara sel iPSC dan ESC, keunggulan teknologi iPSC sekaligus tantangan dalam aplikasinya.